Determination of Serum Myeloperoxidase (MPO) and lactate dehydrogenase (LDH) as a tumour Marker in Chronic Myeloid Leukaemia (CML) - Khitam Abdul Wahhab Ali; Abeer Anwer Ahmed; Suhad Taha Mohammed (Journal of the Pakistan Medical Association)
Objective: To evaluate the efficacy of serum myeloperoxidase and lactate dehydrogenase levels as tumour markers in chronic myeloid leukaemia patients after one-year treatment with tyrosine kinase inhibitors. Method: The case-control study was conducted at the College of Medicine, Mustansiriyah University, Baghdad, Iraq, in collaboration with the National Centre of Haematology, Baghdad, from December 2019 to April 2020. The cases comprised chronic myeloid leukaemia patients aged greater than or equal to18 years who had completed one-year treatment with tyrosine kinase inhibitor. They were divided into two groups on the basis of major molecular response. Group 1 patients had major molecular response >0.1%, while group 2 patients had major molecular response <0.1%. Group 3 had healthy controls matched for age and gender. Serum myeloperoxidase and lactate dehydrogenase concentrations were measured using enzyme-linked immunosorbent assay. Data was analysed using SPSS 25. Results: Of the 88 subjects, 32(36.4%) were in group A with mean age 44.9±12.6 years, 26(29.5%) were in group B with mean age 48.23±10.6 years, and 30(34%) were in group C with mean age 43.1±9.3 years. There was a significant increase in myeloperoxidase and lactate dehydrogenase levels in patient groups compared group 3 controls (p<0.05). Between the patient groups 1 and 2, the difference was significant for myeloperoxidase (p<0.05), but not for lactate dehydrogenase (p>0.05). Conclusion: There was higher oxidative stress in chronic myeloid leukaemia patients. Key Words: Tyrosine Kinase, Oxidative, Peroxidase, Immunosorbent, Leukemia, Myelogenous, Chronic, BCR-ABL, Lactate Dehydrogenases, Tumour